1988
DOI: 10.1128/aac.32.5.626
|View full text |Cite
|
Sign up to set email alerts
|

Novel plasmid-mediated beta-lactamase in clinical isolates of Klebsiella pneumoniae more resistant to ceftazidime than to other broad-spectrum cephalosporins

Abstract: Multiresistant Klebsiella pneumoniae strains isolated from three patients in the same intensive care unit were more resistant to ceftazidime than to cefotaxime and aztreonam but remained susceptible to moxalactam and imipenem. Resistance to I-lactams, kanamycin, streptomycin, sulfonamides, and tetracyclines was transferable to Escherichia coli by conjugation and was lost en bloc after treatment with ethidium bromide. Agarose gel electrophoresis of wild types and transconjugants indicated that these resistances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…The first nosocomial outbreaks caused by ESBL-producing strains occurred in 1985 in France (26,34). Klebsiella pneumoniae was the ESBL-producing enterobacterium most frequently isolated from clinical specimens, but E. aerogenes has recently emerged as an important hospital opportunist.…”
Section: Discussionmentioning
confidence: 99%
“…The first nosocomial outbreaks caused by ESBL-producing strains occurred in 1985 in France (26,34). Klebsiella pneumoniae was the ESBL-producing enterobacterium most frequently isolated from clinical specimens, but E. aerogenes has recently emerged as an important hospital opportunist.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analysis (30) and nucleotide sequence determination (29) of blaTEM-3, the structural gene for the enzyme, indicated that the P-lactamase was a double point mutation of TEM-2 penicillinase and was therefore redesignated TEM-3 (30). Since then, similar enzymes of either the SHV type (5,9) or the TEM type (3,8,22,24) have been detected among members of the family Enterobacteriaceae. The epidemic aspect of this resistance, the fact that it involves recent cephalosporins and monobactams, and the mechanism of substrate range expansion by point mutations in well-known penicillinases prompted us to study the distribution of TEM P-lactamases in strains of enterobacteria and to develop techniques for the rapid detection and characterization of new variants.…”
mentioning
confidence: 99%
“…Molecular analysis (30) and nucleotide sequence determination (29) of blaTEM-3, the structural gene for the enzyme, indicated that the P-lactamase was a double point mutation of TEM-2 penicillinase and was therefore redesignated TEM-3 (30). Since then, similar enzymes of either the SHV type (5, 9) or the TEM type (3,8,22,24) …”
mentioning
confidence: 99%
“…and members of the family Enterobacteriaceae have been documented (6). Since the late 1980s, extended-spectrum ␤-lactamases (ESBLs) derived from TEM-and SHV-type penicillinases capable of hydrolyzing the oxymino-cephalosporins have been spreading globally, mainly in the Enterobacteriaceae, including Klebsiella pneumoniae and Escherichia coli (5,23,29). Moreover, various non-TEM-, non-SHV-type class A ␤-lactamases exhibiting extended-spectrum activities, including CTX-M-type (13,31,38,39,41), SFO-type (18), VEB-type (12,20,25), and GES-type (10,11,19,24,28,37) ␤-lactamases, have also been reported in various gram-negative bacilli.…”
mentioning
confidence: 99%